Islamic Family Law in Facing the Widespread Phenomenon of Siri Marriage: Legal and Social Implication - Dedi Dedi; Dadan Dadan; Aa Hendra; Syafi'i Syafi'i (Journal of Nafaqah, 2024)
The purpose of this study is to examine in depth the position of children from siri marriages according to the constitution in force in Indonesia and to analyze the legal position of illegitimate children from siri marriages as heirs according to civil law and Islamic law. The research method used is a literature study (Information and Reference Study, abbreviated as SIR) by reviewing various literature, articles, journals, and policies related to the phenomenon of siri marriage in the context of Islamic family law. This method was chosen because of its descriptive and analytical nature, where the study emphasizes more on collecting and analyzing various relevant secondary sources to answer existing problems. The results of the study show that siri marriages, although valid according to Islamic law, have significant legal and social implications. From the perspective of Islamic family law, siri marriages often ignore aspects of protecting the rights of women and children that should be guaranteed in the country's legal system. The legal implications of siri marriages include difficulties in obtaining birth certificates for children born from the marriage, which has an impact on access to education and health services. In addition, wives in unregistered marriages do not have the same legal protection as in officially registered marriages, making them vulnerable to injustice in terms of inheritance rights, maintenance, and protection from domestic violence. From a social perspective, unregistered marriages can cause stigma and discrimination against the women and children involved.